DYNAMIC ROUTING METHOD SUPPORTING QUALITY OF SERVICE IN MOBILE NETWORKS WITHOUT INFRASTRUCTURE - Klimenko, I. A. (Problems of Informatization and Control, 2021)
A method of dynamic routing is proposed and substantiated, which, due to the formation of a hierarchical structure of the network and the use of the most efficient routing algorithms at each level of the hierarchy, makes it possible to increase the efficiency of routing in mobile networks without a fixed infrastructure of the Ad Nose class. Increasing the resilience of virtual connections allows you to provide the required level of service quality in Ad Nose networks.